Administration of Nigella sativa during neonatal and juvenile growth period improved liver function of propylthiouracil-induced hypothyroid rats. (3rd March 2020) - Hosseini, Mahmoud; Ghasemi, Simagol; Hadjzadeh, Mosa Al Reza; Ghorbani, Ahmad; Aghili, Sasan; Aghaei, Azita; Soukhtanloo, Mohammad; Beheshti, Farimah
Abstract: Aim: Propylthiouracil (PTU) is frequently used as an antithyroid medication. It is also commonly used to induce hypothyroidism in rodents. PTU administration and hypothyroidism have been shown to affect the liver function. Nigella sativa (NS) has been suggested to have antioxidant and hepatoprotective effects. The objective of this study was to investigate the effects of NS extract administration during neonatal and juvenile growth period on liver function of PTU-induced hypothyroid rats. Methods: The pregnant rats were kept in separate cages. After delivery, the mothers and their offspring were randomly divided into five groups and were treated with the following programs: (1) control; (2) PTU, 0.005% in their drinking water (3–5); PTU-plus 100, 200, or 400 mg/kg NS extract. After lactation period, the offspring continued to receive the same experimental treatment for the first 8 weeks of their life. Ten offspring of each group were randomly selected and weighted at days 10, 30, and 60 after delivery. Their blood samples were collected and the liver tissues were removed. Results: Malondialdehyde (MDA) concentration was increased while, thiol concentration and superoxide dismutase (SOD) and catalase (CAT) activity were decreased in the liver tissues of PTU-treated rats. Serum aspartate amino transferase (AST), alkaline phosphatase (ALK-P), and alanine aminotransferase (ALT) levels in the PTU group were higher than the control group. Treatment with 200 and 400 mg/kg decreased MDA while increasing thiol concentration in the liver tissues compared to the PTU group. Treatment with all doses of the extract decreased serum ALK-P concentration compared with the PTU group. Treatment with 400 mg/kg NS increased CAT and SOD concentrations in the liver tissues and decreased serum AST and ALT concentrations compared to the PTU group. PTU decreased body weight gain of offspring and while, the extract increased the body weight gain of offspring rats. Conclusion: The results of this study demonstrated that administration of NS hydroalcoholic extract in the neonatal and juvenile growth period has an improving effect on the liver function of PTU- induced hypothyroid rats.